1993
DOI: 10.1128/jb.175.5.1384-1391.1993
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of F pilin

Abstract: Transfer of the Escherichia coli fertility plasmid, F, is dependent on expression of F pili. Synthesis of F-pilin subunits is known to involve three F plasmid transfer (tra) region products: traA encodes the 13-kDa precursor protein, TraQ permits this to be processed to the 7-kDa pilin polypeptide, and TraX catalyzes acetylation of the pilin amino terminus. Using cloned tra sequences, we performed a series of pulse-chase experiments to investigate the effect of TraQ and TraX on the fate of the traA product. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 27 publications
(52 reference statements)
1
59
0
Order By: Relevance
“…Thus, 8(Q) seems unlikely to be a processing intermediate that retains part of the TraA signal sequence. Further studies suggest that the 8-kDa form of pilin is derived by modifying the 7-kDa pilin polypeptide (24). As both the Ac-8 and Ac-7 forms of F pilin are present in preparations of purified F pili, the subunits in these filaments may be more heterogeneous than previously thought.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, 8(Q) seems unlikely to be a processing intermediate that retains part of the TraA signal sequence. Further studies suggest that the 8-kDa form of pilin is derived by modifying the 7-kDa pilin polypeptide (24). As both the Ac-8 and Ac-7 forms of F pilin are present in preparations of purified F pili, the subunits in these filaments may be more heterogeneous than previously thought.…”
Section: Discussionmentioning
confidence: 54%
“…Since the products of both traX and traQ appear to be inner membrane proteins (4,48,49), these proteins may normally be associated with each other. TraQ prevents degradation of the traA product and may assist membrane entry of the pilin precursor in a conformation appropriate for signal-peptide cleavage (23,24). A closely associated traX product would then be positioned for catalyzing acetylation of the pilin polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several genes related to plasmid conjugation (traB, -C, -D, -E, -F, -G, -H, -I, -K, -L, -N, -U, -W, -Y, trbB, -C) are present in the pYJ016 sequence. The orientation and arrangement of these tra genes are strikingly similar to those of the F plasmid (Kennedy et al 1977), except that the pYJ016 plasmid lacks traM, -J, -A, -P, -V, -R, -E, -Q, -S, and -T that are involved in pilus formation (Moore et al 1981;Maneewannakul et al 1993) and associated functions. Despite this apparent deficiency, the pYJ016 plasmid was transferred between bacteria by conjugation in the laboratory system (L.-I Hor, unpubl.…”
Section: A Conjugation Plasmidmentioning
confidence: 99%
“…An exception is traQ ; of all the tra genes so far tested, only traQ was required for accumulation of membrane F-pilin. TraQ, itself an inner membrane protein, has been suggested as interacting with the traA gene product in the inner membrane, perhaps to position TraA for processing to mature F-pilin (Maneewannakul et al, 1993). Additional interactions between F-pilin precursors and F-pilin, on the one hand, and both Tra and host proteins on the other, have been postulated (Firth et al, 1996;Paiva and Silverman, 1996), but none of these interactions has been demonstrated.…”
Section: Protein-protein Interactions In the Formation Of F-pilimentioning
confidence: 99%